The Modular Concept in Skull Base Surgery: Anatomical Basis of the Median, Paramedian and Lateral Corridors - Giotta Lucifero, Alice; Fernandez-Miranda , Juan C; Nunez , Maximiliano; Bruno, Nunzio; Tartaglia, Nicola; Ambrosi, Antonio; Marseglia, Gian Luigi; Galzio, Renato; Luzzi, Sabino (Acta Biomedica Atenei Parmensis, 2021)
IntroductionA thorough understanding of skull base anatomy is imperative to perform safely and effectively any skull base approach. In this article, we examine the microsurgical anatomy of the skull base by proposing a modular topographic organization in the median, paramedian, and lateral surgical corridors in relation to transcranial and endoscopic approaches.MethodsFive dry skulls were studied focusing on the intracranial and exocranial skull base. Two lines were drawn parallel to the lateral border of the cribriform plate of the ethmoid bone and foramen lacerum, respectively. Lines 1 and 2 delimited the median, paramedian and lateral corridors of the skull base. The bony structures that formed each corridor were carefully reviewed in relation to the planning and execution of the skull base transcranial and endoscopic approaches.ResultsThe midline corridor involves the crista galli, cribriform plate, planum and jugum sphenoidale, chiasmatic sulcus, tuberculum sellae, sellar region, dorsum sellae, clivus, and foramen magnum. The paramedian corridor includes the fovea ethmoidalis, the root of the lesser and greater sphenoid wing, anterior clinoid process, foramen lacerum, the upper half of the petro-occipital suture, and jugular tubercle. The lateral corridors include the orbital plates, sphenoid wings, squamosal and petrous parts of the temporal bone, caudal aspect of the petro-occipital suture, internal auditory canal, jugular foramen, the sulcus of the sigmoid sinus.ConclusionIn-depth three-dimensional knowledge of skull base anatomy based on the modular concept of the surgical corridors is critical for the planning and execution of the transcranial and endoscopic approaches.